2022
DOI: 10.3390/coatings12010095
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dolomite Rock Powder and Iron Tailings Powder on the Electrical Resistivity, Strength and Microstructure of Cement Pastes and Concrete

Abstract: Dolomite rock powder (the waste stone residue in the production of machine-made sand and stone processing) and iron tailings powder formed by mineral processing industry are solid wastes, which occupy land resources, pollute the environment and release toxic substances without reasonable processing. The dolomite rock powder and iron tailings powder composing a large number of active substances could be advantageous to the cement-based materials. In this study, the electrical resistivity of cement paste and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Secondly, many scholars have also conducted research in the direction of mechanical properties of iron tailings concrete. Liu et al, studied the effects of dolomite powder and iron tailing powder on the resistivity, strength and microstructure of cement paste and concrete, and found that the strength of concrete increased and then decreased with the increase in iron tailing powder admixture [ 15 ]. Lu et al, investigated the effect of curing conditions on the mechanical and microstructural properties of ultra-high-performance concrete incorporating iron tailing powder and found that the strength of concrete first increased and then decreased with the increase in iron tailing powder dosing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, many scholars have also conducted research in the direction of mechanical properties of iron tailings concrete. Liu et al, studied the effects of dolomite powder and iron tailing powder on the resistivity, strength and microstructure of cement paste and concrete, and found that the strength of concrete increased and then decreased with the increase in iron tailing powder admixture [ 15 ]. Lu et al, investigated the effect of curing conditions on the mechanical and microstructural properties of ultra-high-performance concrete incorporating iron tailing powder and found that the strength of concrete first increased and then decreased with the increase in iron tailing powder dosing [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…High utilization solid-waste autoclaved aerated concrete (HUS-AAC) with SAC could effectively improve the stability of HUS-AAC blank and shorten the pre-curing time [17]. The iron tailing powder (ITP) could improve the compactness of the microstructure of cement paste [18]. ITP and SAC have been demonstrated the potential of replacing PC in UHPC production [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Bayesteh et al [16,17] discovered that the cement ratio also has a significant influence on strength, reporting a rapid reduction in compressive strength of cement slurry hardened body with increased cement ratio. Furthermore, the surface of stone powder particles has low activity, which can be hydrated with cement to form single-carbon calcium aluminate and semi-carbon calcium aluminate [18][19][20][21], as well as crystal nuclei, expediting the early cement reaction and improving early strength properties [22,23].…”
Section: Introductionmentioning
confidence: 99%